Energia eólica na economia cearense: uma análise insumo-produto - Cavalcante, Karlos Vilker Salviano (2024)
Solar energy plays a fundamental role in a state with vast wind potential throughout most of the year. Ceará stands out as one of the Brazilian states with the greatest wind potential, giving wind-generated energy a crucial role in its energy matrix. In addition to being a clean and renewable source, wind energy plays a vital role in energy security by diversifying sources of supply and reducing dependence on fossil fuels. Through investments in wind infrastructure and technology, Ceará strengthens its economy, creates jobs, and promotes sustainable development.The analysis conducted in this dissertation highlights the distinction of wind energy from the general energy subset, through an input-output matrix, revealing its importance and potential to drive regional economic development. Wind energy stands out with a high total multiplier, ranking below only key sectors such as petroleum refining and information and communication. These results indicate that, despite its initially smaller contribution to total production, the indirect effects of wind energy are substantial, robustly driving other sectors. Investments in innovation and technology in wind energy generate positive externalities, strengthening research, development, infrastructure, and productive capacity throughout the state. Furthermore, the expansion of this sector creates jobs and income in various areas, increasing demand for goods and services and contributing to sustainable economic growth.